MycoWiki: Functional annotation of the minimal model organism Mycoplasma pneumoniae - Elfmann, Christoph; Zhu, Bingyao; Pedreira, Tiago; Hoßbach, Ben; Lluch-Senar, Maria; Serrano, Luis; Stülke, Jörg (Frontiers in Microbiology, 2022)
The human pathogen Mycoplasma pneumoniae is viable independently from host cells or organisms, despite its strongly reduced genome with only about 700 protein-coding genes. The investigation of M. pneumoniae can therefore help to obtain general insights concerning the basic requirements for cellular life. Accordingly, M. pneumoniae has become a model organism for systems biology in the past decade. To support the investigation of the components of this minimal bacterium, we have generated the database MycoWiki (http://mycowiki.uni-goettingen.de). MycoWiki organizes data under a relational database and provides access to curated and state-of-the-art information on the genes and proteins of M. pneumoniae. Interestingly, M. pneumoniae has undergone an evolution that resulted in limited similarity of many proteins to proteins of model organisms. To facilitate the analysis of the functions of M. pneumoniae proteins, we have integrated structure predictions from the AlphaFold Protein Structure Database for most proteins, structural information resulting from in vivo cross-linking as well as protein-protein interactions based on a global in vivo study. MycoWiki is an important tool for the systems and synthetic biology community that will support the comprehensive understanding of a minimal organism as well as the functional annotation of so far uncharacterized proteins.